Diagnostics to support the control of scabies-Development of two target product profiles. - Michael Marks; Jodie McVernon; James S McCarthy; Wendemagegn Enbiale; Christopher Hanna; Olivier Chosidow; Daniel Engelman; Kingsley Asiedu; Andrew Steer (Public Library of Science (PLoS), 2022)
Background Scabies was added to the WHO NTD portfolio in 2017 and targets for the control of scabies were included in the 2021-2030 WHO NTD roadmap. A major component of scabies control efforts a strategy based on mass drug administration (MDA) with ivermectin. Currently diagnosis of scabies relies on clinical examination with a limited role for diagnostic testing. Under the recommendation of the WHO Diagnostic Technical Advisory Group (DTAG) for Neglected Tropical Diseases, a working group was assembled and tasked with agreeing on priority use cases for and developing target product profiles (TPPs) for new diagnostics tools for scabies. Methodology and principal findings The working group convened three times and established two use cases: establishing if the 10% threshold for mass drug administration had been reached and if the 2% threshold for stopping mass drug administration has been achieved. One subgroup assessed the current diagnostic landscape for scabies and a second subgroup determined the test requirements for both use cases. Draft TPPs were sent out for input from stakeholders and experts. Both TPPs considered the following parameters: product use, design, performance, configuration, cost, access and equity. The group considered the use of the tests as a single step process or as part of a two step process following initial clinical examination. When used a single step test (the ideal scenario) for starting MDA a new diagnostic required a sensitivity of ≥92% and a specificity of ≥98%. When used a single step test (the ideal scenario) for stopping MDA a new diagnostic required a sensitivity of ≥80% and a specificity of ≥99%. Conclusions The TPPs developed will provide test developers with guidance to ensure that novel diagnostic tests meet identified public health needs.